Time capsules of biodiversity: Future research directions for groundwater-dependent ecosystems of the Great Artesian Basin - Beasley-Hall, P. G.; Murphy, N. P.; King, R. A.; White, N. E.; Hedges, B. A.; Cooper, S. J. B.; Austin, A. D.; Guzik, M. T. (Frontiers in Environmental Science, 2023)
The Great Artesian Basin of Australia represents one of the largest and deepest basins of freshwater on Earth. Thousands of springs fed by the Basin are scattered across Australia’s arid zone and often represent the sole sources of freshwater for thousands of kilometers. As ‘islands’ in the desert, the springs support endemic fauna and flora that have undergone millions of years of evolution in almost total isolation. Here, we review the current body of knowledge surrounding Great Artesian Basin springs and their significance from ecological and evolutionary perspectives using South Australian spring wetlands as a case study. We begin by identifying the status of these springs as critical sources of groundwater, the unique biodiversity they support, and their cultural significance to the Arabana people as Traditional Custodians. We then summarize known threats to the springs and their biota, both exogenous (e.g., groundwater drawdown by humans) and endogenous (e.g., overabundant native species), and the potential impacts of such processes. Finally, considering the status of these at-risk habitats as time capsules of biodiversity, we discuss lessons that can be learnt from current conservation and management practices in South Australia. We propose key recommendations for improved biodiversity assessment and monitoring of Great Artesian Basin springs that apply to the system nationwide, including 1) enhanced legal protections for spring biota; 2) an increase in taxonomic funding and capacity; 3) improvements to biodiversity monitoring methods, and 4) opportunities for reciprocal knowledge-sharing with Aboriginal peoples when conducting biodiversity research.